Ilija Garasanin: Nacertanije and Nationalism - Manetovic, Edislav (The Historical Review/La Revue Historique, 2007)
This paper analyses the national thought and policies of Ilija Garasanin. Garasanin was the first to write a Serbian national programme, Nacertanije, that envisioned an independent Serbian state. His ideas and policies remain highly controversial. While some scholars argue that Garasanin was an inclusive Yugoslavist, others maintain that he was an exclusive Serbian nationalist seeking a Greater Serbia. Both arguments assume that the South Slav nations are pre-modern social phenomena. In contrast, this paper suggests that a modernist perspective of nations and nationalism provides a far more coherent and nuanced interpretation of Garasanin. Garasanin was a Serbian, not a Yugoslav, nationalist. But his nationalism was inclusive not exclusive. Inclusion was a precondition for social stability of the large state he wanted to forge. Garasanin was also illiberal. Establishing a state in a predatory inter-state environment required suppressing individual liberties. Insecurity caused by a Hobbesian world political system structured the content of Garasanin’s nationalism.